Dispossessed by the law? Effects of the decree 68, 1916 of the magdalena government on the arhuaco people (2016)
This article reflects on the ambiguous role of the law in the administration of indigenous people in Colombia during the first decades of the twentieth century, based on the Decree 68 of 1916 promulgated by the Governor of Magdalena Grande. From the point of view of its promoters, this legal device sought to address a number of requests made by the Arhuaco, about the recognition of their own authorities, protection against economic exploitation by settlers, and the strengthening of cultural autonomy. But from the indigenous point of view, the decree led to a massive loss of autonomy, which can be conceptualized as part of a dispossession process. Despite the rhetoric of justice and equity, the practical consequences of the rule were contrary to Arhuaco requests. In contradiction with the principles and objectives claimed, the decade of the 1920s was one of the most violent for this population.